FUNGSI KOMUNIKASI PIMPINAN DALAM MENINGKATKAN KINERJA PEGAWAI PADA UNIT PELAKSANA TEKNIS BADAN PENGELOLA AIR BERSIH (UPT BPAB) DINAS PEKERJAAN UMUM KABUPATEN PELALAWAN - Donna Riza; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Leader is a critical success factor for it’s regency or company. The success of leadership in a regency or company is depend on the leader quality. A leader must have great proficiency to implement leadership. So that the agency or company can move towards the goals the to be achieved. Operational Technical of Clean Water Management (UPT BPAB) of Ministry Public Works at Pelalawan Regency is an agency that in charge of distributing clean water for Pelalawan Community. In practice, UPT BPAB of Pelalawan Regency confronted with some problems regarding the level of customer satisfaction on the employe performance of UPT BPAB . Therefore, UPT BPAB must improve leadership communication to increase employe performance. The goal of this research is to determine the function of leadership communication and the interaction from to increase employee performance of UPT BPAB of Ministry Public Works of Pelalawan Regency. The research method using in this research is quallitative descriptive sampling technique. The informants in this research are 5 people that selected based on the official department, which is the head of UPT BPAB of Ministry of Public Works of Pelalawan Regency, 2 employee from administration department, 2 employee from production department. The techniques of data collection in this research are using interview, documentation, and observation. The techniques of data analysis are based on Huberman and Miles interactive model. Data validity checking are using the exstension of participation and triangulation. This research shows that the function of leader communication in order to increase employee performance at UPT BPAB of Ministry Public Works of Pelalawan Regency is Fairly good. With vertical and horizontal communication, the leader can deliver clear instruction and the employee can responsible in their duties. The interaction forms in order to increase employee performance are using discussion, memo, and direct communication.Keywords : Leader Communication, Performance, Employee.